Modelos para expressar a densidade da madeira, biomassa e carbono de florestas nativas em Minas Gerais - Páscoa, Kalill José Viana da (2018)
Native forests have an important role in society, including sequestration and carbon storage in different biomass compartments. Knowing the size of this service is challenging, but necessary, due to current climate change scenarios, because they help to understand the role of forests in regulating CO2 levels in the atmosphere and justify the importance their preservation. Knowing the carbon stock of a forest depends on the knowledge of their biomass, which consequently depends on the variation of the wood basic density.In this scenario, the objective of this study was to conduct a comprehensive study about the sampling and calculation of wood basic density of native trees,modeling of biomass and spatial distribution of carbon stored in forest remaining in the Rio Grande watershed,state of Minas Gerais, Brazil.The analysis of the sampling for studies about wood basic density indicates that from 30 trees occurs the stabilization of the coefficient of variation, so smaller samples should be avoided.The average of wood basic density in a tree is highly correlated with the density observed at 25 and 50% of its height, which is a good indicator for nondestructive sampling. The total biomass of the sampled trees indicate that, on average, 55.7% is allocated on the trunk, 24.5%on thick branches, 13.7% on fine branches and 6.6% on leaves. The total biomass was highly correlated with values of diameter, total height, crown area and wood basic density, where the models that used these variables together presented excellent results. Carbon stock estimates for the watershed were 118.8 Tg, which is equivalent to 436.0 Tg carbon dioxide, with a market value of R$ 13.4 billion.The highest values were found in the Rain forest vegetation type (90 Mg ha-1) and lower in the Savanna (30 Mg ha-1), as expected. The Rain forest is characterized as a vegetation type belonging to the Atlantic Forest biome that stands out for having a high and dense tree component with a well-populated sub-forest, while the Savanna is a type of xeromorphic vegetation that develops in poor soils varying in size from grassy to arboreal with tortuous branches. In relation to the total, Atlantic Forest (Rain forest and Semideciduous forest) stocks 57.9% of the carbon and the Savanna 31.8%. Of this total, 84% are in forests located in private properties, against 16% in conservation units.Of the carbon stored in private properties, 62% is located in small properties, 24.7% in mean and 13.3% in large properties, indicating the importance of conservation of forest remaining, by the reduction of deforestation and increase of forest area.